From start to finish: amino-terminal protein modifications as degredation signals in plant - Gibbs, Daniel J.; Bailey, Mark; Tedds, Hannah M.; Holdsworth, Michael J. (Wiley, 2016)
The amino- (N-) terminus (Nt) of a protein can undergo a diverse array of co- and posttranslational modifications. Many of these create degradation signals (N-degrons) that mediate protein destruction via the N-end rule pathway of ubiquitin-mediated proteolysis. In plants, the N-end rule pathway has emerged as a major system for regulated control of protein stability. Nt-arginylation-dependent degradation regulates multiple growth, development and stress responses, and recently identified functions of Nt-acetylation can also be linked to effects on the in vivo half-lives of Nt-acetylated proteins. There is also increasing evidence that N- termini could act as important protein stability determinants in plastids. Here we review recent advances in our understanding of the relationship between the nature of protein N-termini, Nt- processing events and proteolysis in plants.